ANALYSIS OF THE EFFECT OF UNDERSTANDING, SOCIALIZATION, SERVICE QUALITY, AND MODERNIZATION OF ADMINISTRATIVE SYSTEM ON TAXPAYER COMPLIANCE WITH AWARENESS AS AN INTERVENING AT KPP PRATAMA MEDAN POLONIA - Prasetya Putra Bangsa; Iskandar Muda; Khaira Amalia Fachrudin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to determine and analyze the influence of Understanding, Socialization, Quality of Tax Service, and Modernization of the Administrative System on Taxpayer Compliance with Awareness as Intervening at KPP Pratama Medan Polonia. The sample in this study was 100 individual taxpayers registered at KPP Pratama Medan Polonia. The data analysis technique used was Inferential statistical analysis - Partial Least Square (PLS). The results of this study indicate that understanding socialization has a significant effect on awareness. At the same time, the quality of tax service and modernization of the administrative system do not significantly affect awareness. Understanding does not significantly affect taxpayer compliance, while socialization, quality of tax service, administrative system modernization, and awareness significantly affect taxpayer compliance. Indirectly, taxpayer awareness can mediate socialization on taxpayer compliance, and indirect awareness cannot mediate understanding, quality of tax service, and modernization of the administrative system on taxpayer compliance.